UJI EFEKTIVITAS KOTORAN SAPI DALAM REMEDIASI TANAH TOP SOIL YANG TERCEMAR OLI - Tuti Marlina; Husnawati Yahya; Abd Mujahid Hamdan (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2021)
Oil waste that enters the soil will cause damage to the soil. Bioremediation is an alternative to hazardous waste treatment which is relatively more economical, easy and environmentally friendly. This technology utilizes microbial activity to treat polluted soil. Cow dung is an organic material that contains many microbes and also contains good nutrition for microbial growth. Cow dung contains several microorganisms such as bacteria (Bacillus sp, Lactobacillus sp and Corynebacterium sp), fungi (Trichoderma sp and Aspergillus sp), protozoan and yeast species (Candida sp and Saccharomyces sp). Cow dung in this study acts as a bioactivator and a source of nutrients for microbes in degrading Total Petroleum Hydrocarbon (TPH) in oil-contaminated soil. This study aims to determine the effect of adding cow dung on bioremediation of oil-contaminated soil. This study consisted of six (6) treatments, namely the concentration of cow dung with variations in concentrations of 0 gr, 20 gr, 40 gr, 60 gr, 80 gr, and 100 gr on each soil of 300 gr and processing time for 30 days and analyzed 2 times a day. In this study, measurements of pH and TPH values ​​were carried out. The results of the analysis showed that the addition of cow dung with a concentration of 100 gr on 300 gr of soil was able to reduce the TPH value from 3.6% to 0.2%, with the effectiveness of reducing TPH by 86.66% within 30 days. Based on the results of the analysis using the Simple Linear Regression Test, it was stated that the bioremediation time and the addition of the concentration of cow dung had an effect on the decrease in the TPH value.